Substance and procedure in equity - Swadling, W (LexisNexis, 2016)
There is much confusion within the law of Equity over issues of substance and procedure. Sometimes, procedural issues are mistaken for ones of substance; at other times, substantive issues are seen as procedural. So far as the former are concerned, there is misunderstanding regarding the statutory rules of admissibility of evidence to prove an allegation of a declaration of trust, the judge-made rules governing the burden of proof at trial of declarations of trust, the so-called liability of persons to account as 'constructive trustees', the rule that 'equity acts in personam', and the tendency to equate the availability of equitable relief with the existence of equitable property rights. With regard to issues of substance being seen as procedural, there is equitable estoppel, tracing, and the notion that 'presumed' resulting trusts are concerned with the filling of 'evidential lacunae'. The article demonstrates how such wrongful classifications lead both courts and commentators into error.